(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2014)
The wear of machines and mechanisms after rubbing is a major concern. The costs of manufacturing and restoration parts for agricultural machinery are enormous such as the trunnions pinions of hydraulic pumps. Finishing treatment antifriction without abrasive (FTAA) is the existing method of manufacturing and restoration, but it has disadvantages like low work efficiency and the frequent replacement of the instrument. That is why a new method of FTAA parts type ’’tree’’ has been developed called vibratory finishing treatment antifriction without abrasive, (VFTAA) method. The study was conducted at the laboratory of the State Technical University of Kirovograd (Ukraine) where turn 16K20, the profilograph-profilometer "Talysurf-5", the scanning electron microscope REM-106I, friction machine MI-1M and the stand KI-28097-02M were used respectively for machining, study of micro relief before and after the VFTAA, microstructure, wear resistance and the determination of the break-in period of parts. The results showed that the VFTAA helped reduce the roughness Ra of the samples studied by half compared to the samples processed by polishing and 1.3 times compared to those treated with the FTAA, the break-in period has been reduced four times , this leads to an increase in the life of the hydraulic pump. This technology can be recommended for manufacturing and repair of hydraulic units of agricultural machineries. DOI: http://dx.doi.org/10.3329/ijarit.v4i1.21101 Int. J. Agril. Res. Innov. & Tech. 4 (1): 98-101, June, 2014